Miami Blue, Cyclargus thomasi bethunbakeri (Comstock & Huntington) (Insecta: Lepidoptera: Lycaenidae) - Jaret C. Daniels (EDIS)
EENY-386, a 3-page illustrated fact sheet by Jaret C. Daniels, describes this endangered small brightly colored butterfly which inhabits tropical hardwood hammocks and their associated margins, beachside scrub and tropical pine rocklands. Includes selected references. Published by the UF Department of Entomology and Nematology, September 2006.